Digital Image Filtering with New Generalized Order-k Jacobsthal Numbers - Ahmed, Hossen; Daşdemir, Ahmet (Prof. Marin Drinov Publishing House of BAS (Bulgarian Academy of Sciences), 2022)
In this paper, a new generalized order-k Jacobsthal and Jacobsthal–Lucas numbers are investigated and used in the digital image processing for filtering of the image. The Gaussian, Morphological operation with “Motion”, Morphological operation with “Disk” specification, Poisson method and Jacobsthal method is used for the filtering. The Structural similarity, Multiscale structural similarity and Peak SNR are used for evaluation of the results. For implementation of the proposed method the Matlab 2021a version is used.